Study on the Implications of Academic Competency Mismatch at the Office of the Regional House of Representatives of Gorontalo Regency (2019-2024 Period) - Dewi Clara Ladiku; Srihandayani Suprapto; Franky Djafar (Universitas Muhammadiyah Palu, 2025)
This study aims to analyze the implications of academic competency mismatch at the Gorontalo Regency DPRD Office in the 2019–2024 period. Competency mismatch occurs when an employee's educational qualifications are not in line with job demands, which has an impact on job performance, satisfaction, and collaboration. Referring to Mayo's theory, individual development and social interaction in the work environment are key factors in achieving optimal performance. Through interview and documentation methods, it was found that education and training are important investments in shaping human resource competencies. However, the mismatch between employees' abilities and the tasks carried out is still an obstacle that can reduce productivity and work motivation. A supportive work environment and attention from superiors have been proven to increase employee morale, while internal conflicts are actually obstacles. This research emphasizes the importance of improving the quality of human resources and adjusting competencies to organizational needs to support the achievement of professional and competitive governance.